Super color purity green organic light-emitting diodes with ZrO2/zircone nanolaminates as a distributed Bragg reflector deposited by atomic layer deposition. (16th December 2016) - Zhang, Jianhua; Zhang, Hao; Zheng, Yanqiong; Wei, Mengjie; Ding, He; Wei, Bin; Zhang, Zhilin
Abstract: ZrO2 /zircone nanolaminate thin films fabricated by atomic layer deposition were used for a distributed Bragg reflector (DBR) in green organic light-emitting diodes (OLEDs). It is found that the novel ZrO2 /zircone DBR structure significantly improves the light purity of green OLEDs without interfering with intrinsic electroluminescence properties. The full width at half maximum (FWHM) of the EL spectral band for the green OLEDs decreases with respect to increasing the ZrO2 /zircone pairs. The FWHMs of OLEDs with 0, 2, 4, and 6 pairs of ZrO2 /zircone layers are 72 nm, 48 nm, 24 nm, and 12 nm, respectively. A super-narrow FWHM of 12 nm is achieved by using six pairs of the DBR structure. The EQE is increased from 10.7% to 16.1% with four pairs of ZrO2 /zircone layers.